Photonic Integration on the Hybrid Silicon Evanescent Device Platform. (24th April 2008) - Park, Hyundai; Fang, Alexander W.; Liang, Di; Kuo, Ying-Hao; Chang, Hsu-Hao; Koch, Brian R.; Chen, Hui-Wen; Sysak, Matthew N.; Jones, Richard; Bowers, John E.
Abstract : This paper reviews the recent progress of hybrid silicon evanescent devices. The hybrid silicon evanescent device structure consists of III-V epitaxial layers transferred to silicon waveguides through a low-temperature wafer bonding process to achieve optical gain, absorption, and modulation efficiently on a silicon photonics platform. The low-temperature wafer bonding process enables fusion of two different material systems without degradation of material quality and is scalable to wafer-level bonding. Lasers, amplifiers, photodetectors, and modulators have been demonstrated with this hybrid structure and integration of these individual components for improved optical functionality is also presented. This approach provides a unique way to build photonic active devices on silicon and should allow application of silicon photonic integrated circuits to optical telecommunication and optical interconnects.